Privacy Protection in Healthcare Information system using Heterogeneous Public Cloud Authorities (International Journal of Food and Nutritional Sciences, 2022)
The rapid development of the Internet of Things (IoT) has led to the emergence of more and more novel applications in recent years. One of them is the e-health system, which can provide people with high-quality and convenient health care. Meanwhile, it is a key issue and challenges to protect the privacy and security of the user’s personal health record. Some cryptographic methods have been proposed such as encrypt user’s data before sharing it. However, it is complicated to share the data with multiple parties (doctors, health departments, etc.), due to the fact that data should be encrypted under each recipient’s keys. Although several (t, n) threshold secret sharing schemes can share the data only need one encryption operation, there is a limitation that the decryption private key has to be reconstructed by one party. To offset this shortcoming, in this paper, we propose an efficient identity-based distributed decryption scheme for personal health record sharing system. It is convenient to share their data with multiple parties and does not require reconstructing the decryption private key. We prove that our scheme is secure under chosen-cipher text attack (CCA). Moreover, we implement our scheme by using the Java pairing-based cryptography (JPBC) library on a laptop and an Android phone. The experimental results show that our system is practical in the electronic personal health record system.In the present-day cloud computing Private sensitive data service utilization of independent and corporate needs enormous computational power and scalability over data storage facilities to encourage big data utility applications power domains like insurance, public Health Care, and Research and Development areas needs to focus on Security attributes. An electronic insurance record or sensitive personal health record or client-specific personal information needs to get safeguarded from another id third party uses of the public cloud which could be done by adopting data transformation schemes. In the domain of cloud computing in which data as a service place a demanding situations over shared data utilization and inter-access facilities. Data access policies that are been empowered over insensitive data are being sufficiently scaled up whereas methodologies to interact sensitive information of data providers are to be enhanced to the present day security requirements. So user specific sensitive information is to get privacy-preserving by adopting effective and efficient encryption methodologies and not encouraging limitations over data utilization strategies which brings a great reliability and trustworthiness of personal sensitive information. Electronic health records or medical information or personal insurance policy reports or preparatory personal employee information to get maintained following high level security strategies so as to bring reliability and usability in a more wider boundaries. In order to facilitate a wide scalability, attribute based encryption is been adopted facilitating authorized methodologies to be performed over integrated security policies in multiple authority architectural platforms. Infocus of improvising security strategies by adopting optimal encryption methodologies main bring a overhead are barrier gates to search techniques of encrypted data formats.